Des de la concepció medieval fins a la narració actual: El reliquiari a través de l'obra de Joan Millet. - MARQUÉS SERRA, DAVID (Scripta, 2019)
This investigation addresses the theme of the reliquary, originally destined to the veneration of sacred elements, and goes in depth in the study of its constant evolution to the contemporary era, through the production of Joan Millet Bonet. Thus, an intertemporal comparison is proposed with the aim of extracting the possible links that can offer us the different discursive keys necessary for the object to maintain its inherent nature. In this way and inevitably, we allude to the tangential spiritual issues that accompany the sacred object, both in ancient times and the present day. All this, necessarily, configures the environments in which the reliquaries are circumscribed in their different times and, in turn, by extension, also condition and shape their formal and aesthetic possibilities.